2011
DOI: 10.20996/1819-6446-2011-7-5-567-573
|View full text |Cite
|
Sign up to set email alerts
|

The Adherence to Recommended Therapy in Patients After Acute Coronary Syndrome, and Risk of Cardiovascular Complications Within a Year After Hospital Admission

Abstract: Приверженность лечению -это степень, с кото-рой пациент готов выполнять предписания врача, причем подразумевается добровольное активное взаимоприемлемое взаимодействие пациента и врача для достижения терапевтического эффекта. Низкая приверженность выполнению врачебных назначений и рекомендаций является основным барьером на пути успешного лечения и проблемой, которую должны пытаться решить медицинские ра-ботники [1][2][3].По данным литературы, каждый четвертый пациент не придерживается предписанной лечащим врач… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Interventions aimed at increasing adherence to treatment in the short and medium term provide a significant positive return on primary and secondary prevention investment. At the same time, special education programs aimed at increasing treatment adherence reduce their effectiveness over time and are ineffective in the long-term perspective [63]. (2A)…”
Section: ключевые слова: приверженность количественная оценка лекарственная терапия медицинское сопровождение модификация образа жизни упmentioning
confidence: 99%
“…Interventions aimed at increasing adherence to treatment in the short and medium term provide a significant positive return on primary and secondary prevention investment. At the same time, special education programs aimed at increasing treatment adherence reduce their effectiveness over time and are ineffective in the long-term perspective [63]. (2A)…”
Section: ключевые слова: приверженность количественная оценка лекарственная терапия медицинское сопровождение модификация образа жизни упmentioning
confidence: 99%
“…Помимо этого, недавно проведенные исследования проде-монстрировали связь между недостаточной привер-женностью к лечению и возрастанием сердечно-со-судистого риска. Согласно полученным данным низ-кая приверженность ассоциируется с трехкратным по-вышением риска развития ССО [10]. По данным аме-риканских исследователей использование совре-менных препаратов для первичной и вторичной про-филактики ССЗ позволило бы снизить сердечно-со-судистую смертность на 50%, но мета-анализ 44 проспективных исследований показал, что привер-женность длительной терапии ССЗ составляет не бо-лее 60%, что не позволяет в ожидаемой степени рассчитывать на такое снижение [11].…”
Section: Adherence To Treatment Of Hypertension and Dyslipidemia привunclassified
“…Research has shown that longterm adherence to any treatment of any disease does not exceed 50% [2]. In a series of studies conducted on adherence to treatment, it was shown that the degree of adherence ranged from 43-78% [3,5,10,11]. It has been established that 1/3 of the patients discontinue the recommended treatment within 12 months after a cardiovascular event.…”
mentioning
confidence: 99%
“…It has been established that 1/3 of the patients discontinue the recommended treatment within 12 months after a cardiovascular event. Wherein, low treatment adherence was associated with a significant increase in the risk of cardiovascular complications [1,3,4,7,8]. Adherence to pharmacotherapy depends on many factors.…”
mentioning
confidence: 99%